Interactive effect of branch source-sink ratio and leaf aging on photosynthesis in pistachio - Marino, Giulia; Guzmán-Delgado, Paula; Santos, Emily; Adaskaveg, Jaclyn A.; Blanco-Ulate, Bárbara; Ferguson, Louise; Zwieniecki, Maciej A.; Fernández-Suela, Eduardo (Frontiers in Plant Science, 2023)
We investigated the impact of branch source-sink ratio on leaf seasonal photosynthetic performance in pistachio (Pistacia vera) trees. Tree source-sink ratio has a predominant and complex impact on tree performance and can affect multiple physiological process including vegetative and reproductive growth, water and nutrient use, photosynthesis, and productivity. In this study, we manipulated the branch level source-sink ratio by reduction of photosynthetic activity (partial branch defoliation) or thinning branch fruit load early in the growing season (after fruit set). We then characterized the leaf photosynthetic light response curves through leaf aging in pistachio tree branches. In addition, we determined changes in leaf non-structural carbohydrates (NSC) and nitrogen (N) concentration. In leaves with high source-sink ratios, there was a gradual decrease in maximum net photosynthetic rate (ANmax) over the growing season, while in branches with low source-sink ratios, there was a sharp decline in ANmax in the first two weeks of August. Branches with high-sink showed an up-regulation (increase) in photosynthesis toward the end of July (at 1,500 growing degree days) during the period of rapid kernel growth rate and increased sink strength, with ANmax been about 7 μmol m-1 s-1 higher than in branches with low-sink. In August, low source-sink ratios precipitated leaf senescence, resulting in a drastic ANmax decline, from 25 to 8 μmol m-1 s-1 (70% drop in two weeks). This reduction was associated with the accumulation of NSC in the leaves from 20 to 30 mg g-1. The mechanisms of ANmax reduction differ between the two treatments. Lower photosynthetic rates of 8-10 μmol m-1 s-1 late in the season were also associated with lower N levels in high-sink branches, suggesting N remobilization to the kernels. Lower photosynthesis late in the season was associated with lower respiration rates in low-source branches, indicating prioritization of assimilates to storage. These results provide insight into the physiological factors influencing photosynthesis in relation to source-sink balance and management implications. The seasonal changes in sink strength exerted by the growing fruits in species with strong fruit sinks like pistachio may greatly affect the tree’s physiological response to environmental and management factors.